Indonesian adolescents’ EFL reading comprehension: Gender differences and the influence of parental background - Aditomo, Anindito; Hasugian, Eko Jatmiko (Universitas Pendidikan Indonesia, 2018)
This article presents findings on gender differences and the influence of family background on students’ EFL reading comprehension in Indonesia. A total of 265 students (48.3% female, average age 13.6 years) from grades 7 to 8 in four schools anonymously completed an EFL reading comprehension test. In contrast to prior findings showing girls’ advantage of first language literacy, this study found no gender differences in EFL reading comprehension. In line with prior studies on the effect of socioeconomic status on student achievements, parents’ level of education influenced students’ EFL reading comprehension. For boys, the effect of mother’s education occurred through the provision of literacy resources. For girls, by contrast, the effect occurred through mother’s involvement in their daughters’ reading activities, which in turn encouraged reading engagement and comprehension. These findings underscore the importance of gender-appropriate strategies to facilitate adolescents’ EFL reading engagement and comprehension.